Information on the ballot, voter satisfaction and election turnout - Christoph Sajons (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2016)
If voters do not perceive meaningful differences between parties and candidates, they tend to stay at home or choose by other factors like style or likability. This study examines whether including different kinds of information about the candidates on the ballot affects the satisfaction and turnout of voters in low-profile elections in which most candidates are unknown and party-identification cannot be used to distinguish them. This case often appears in election systems with either intra-party primaries or open lists, in particular at lower institutional levels. The empirical analysis is based on an experimental exit-poll of voters at local elections in two German states in 2014 in which respondents faced a hypothetical election with different information treatments. The main results are: (1) More information on the ballot increases voter satisfaction, but the marginal effect is decreasing. (2) Profession information is particularly useful for voters. (3) This translates directly into a greater willingness to take part in the hypothetical election ('turnout'), especially for individuals unsatisfied with the real election system. (4) The last result can be confirmed with aggregate turnout data of German local elections after reunification.
Keywords: D72; H79; P16; 330; information cues; voter satisfaction; turnout; electoral systems; profession